頭戴式人眼追蹤系統 - 歐陽盟; 邱俊誠; 黃庭緯; 胡俊誠; 莊竣崴 (My University, 2015)
一種頭戴式人眼追蹤系統，其包括第一光源、第一瞳孔影像擷取裝置、第一及第二環境影像擷取裝置、固定裝置以及影像辨別系統。第一光源適於照亮使用者的第一眼。第一瞳孔影像擷取裝置適於擷取來自第一眼中的第一瞳孔影像。第一、第二環境影像擷取裝置分別適於擷取使用者前方的第一、第二環境影像。配置於使用者的頭上的固定裝置將第一光源、第一瞳孔影像擷取裝置、第一及第二環境影像擷取裝置固定於使用者的第一眼的週圍。影像辨別系統適於將第一環境影像以及第二環境影像其中至少一者與第一瞳孔影像進行映對。 A head-mount eye tracking system including a first light source, a first pupil image capturing device, a first and a second environmental image capturing devices, a fixing device and an image identification system. The first light source is applied to illuminate a first eye of a user. The first pupil image capturing device is applied to capture a first pupil image from the first eye. The first and the second environmental image capturing devices are respectively applied to capture a first and a second environmental images in front of the user. The fixing device, disposed on the head of the user, fix the first light source, the first pupil image capturing device, the first and the second environmental image capturing devices around the first eye of the user. The image identification system is applied to map one of the first or the second environmental images to the first pupil image.